2019
DOI: 10.1371/journal.pone.0214817
|View full text |Cite
|
Sign up to set email alerts
|

Wide sensory filters underlie performance in memory-based discrimination and generalization

Abstract: The way animals respond to a stimulus depends largely on an internal comparison between the current sensation and the memory of previous stimuli and outcomes. We know little about the accuracy with which the physical properties of the stimuli influence this type of memory-based discriminative decisions. Research has focused largely on discriminations between stimuli presented in quick succession, where animals can make relative inferences (same or different; higher or lower) from trial to trial. In the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 82 publications
(107 reference statements)
1
26
0
Order By: Relevance
“…The data, thus, suggest that multi-island SIT might represent an adequate behavioral readout of perceptual thresholds. This premise is further supported by the observation that the sit-time incidence percentage for the 860 Hz island of gerbil 2 decreased to baseline at later training sessions, which is indicative of increased frequency identification ability with experience ( Figure 2C, lower panel), which could be explained by an extinction of the prior generalization (Chen et al, 2019). The reason why generalization (and extinction) is seen at 860 Hz, but not 460 Hz might be related to asymmetrical filter broadening and/or the closer logarithmic spacing (Schnupp et al, 2011).…”
Section: Multiple Island Asit Freqmentioning
confidence: 55%
See 1 more Smart Citation
“…The data, thus, suggest that multi-island SIT might represent an adequate behavioral readout of perceptual thresholds. This premise is further supported by the observation that the sit-time incidence percentage for the 860 Hz island of gerbil 2 decreased to baseline at later training sessions, which is indicative of increased frequency identification ability with experience ( Figure 2C, lower panel), which could be explained by an extinction of the prior generalization (Chen et al, 2019). The reason why generalization (and extinction) is seen at 860 Hz, but not 460 Hz might be related to asymmetrical filter broadening and/or the closer logarithmic spacing (Schnupp et al, 2011).…”
Section: Multiple Island Asit Freqmentioning
confidence: 55%
“…Gerbils are generally capable of discriminating even smaller frequency differences than used here (0.4 octaves) when presented in succession ( Klinge and Klump, 2009 ). However, Chen et al (2019) have recently shown that when confronted with a memory-based frequency discrimination task, mice generalize auditory stimuli. Therefore, one plausible explanation to the increased sit-time incidences for 860 Hz is that the gerbils generalized the new presented stimulus initially after introduction of the non-target islands.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm altered gap perception in freely behaving mice, we tested Mbp neo/neo mutants in the ‘AudioBox’ (New Behavior , TSE systems), an automated system for auditory behavioral testing 6973 . Animals were exposed to ‘safe visits’ of one cage corner (Figure S7E), in which a continuous sound was played, and water was always available.…”
Section: Resultsmentioning
confidence: 99%
“…In an inhibitory avoidance task, inhibition of NLGN2 function in the prelimbic region of the mPFC in rats resulted in a persistent disruption of memory retention and an enhancement of immediate early gene expression after a retention trial (90). Last, in an auditory discrimination task, constitutive Nlgn2 KO mice showed decreased avoidance of a punished tone despite normal auditory acuity, indi cating a potential impairment in encoding the valence of the audi tory stimulus (82). To our knowledge, only one study has identified a role for NLGN2 in cognitive functions other than aversive condi tioning, showing that viral overexpression of NLGN2 rescued a stressinduced attention deficit in the fivechoice serial reaction time task (91).…”
Section: Nlgn2 In Cognitive Functionmentioning
confidence: 99%
“…Unlike its consequences for anxiety behaviors, constitutive deletion of Nlgn2 appears to have only very minor effects on sensory func tions. Auditory function as assessed by an acoustic startle response test was unaltered (81), and in an auditory discrimination para digm, auditory acuity as assessed by tone generalization did not differ between wildtype (WT) and Nlgn2 KO mice (82). Similarly, olfactory function was not affected by Nlgn2 deletion (81).…”
Section: Nlgn2 In Sensory Functionsmentioning
confidence: 99%